2002
DOI: 10.1253/circj.66.75
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Blood Pressure Monitoring in Uygur Centenarians

Abstract: t has been shown that the humans living to a very old age have a genetic tendency toward moderate and balanced blood pressure (BP). 1,2 The Uygurs in Xinjiang are a naturally longevous population, surviving to a very old age without any medical treatment or services. There have been studies showing that the Uygur people do live to an older age than other people in the Xinjiang Uygur Autonomous Region of China, 3,4 but these reports have not provided information on the blood pressure (BP) variations, such as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
2
11
1
Order By: Relevance
“…11 This study showed a steady increase in prevalence of hypertension with age with highest percentage of hypertensive subjects among the centenarians (39%).…”
mentioning
confidence: 63%
“…11 This study showed a steady increase in prevalence of hypertension with age with highest percentage of hypertensive subjects among the centenarians (39%).…”
mentioning
confidence: 63%
“…Subject ages were confirmed on the basis of resident registration forms, marital, family, and personal histories conveyed in the native Uygur language. Centenarians were selected as representing Uygur centenarians (18.9/100,000) 4 in the Hotan area if they were ambulant, capable of self-care, and able to hold simple conversation. For all subjects, we obtained physical and routine laboratory examination in the week preceding the study.…”
Section: Study Populationmentioning
confidence: 99%
“…4 The Uygurs in Xinjiang, China, are particularly long-lived. Extreme longevity in humans seems to be associated with numerous factors.…”
Section: Centenarians and Wc Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…These subjects were divided into two groups according to age: a group of Uygur centenarians in Hotan (UCH) (33 subjects; age 100 years) and a group of elderly UEH (100 subjects age 65-70 years). The age of subjects was confirmed through resident registration forms and personal histories (5). The height and weight of subjects were measured before the 24-h ambulatory blood pressure monitoring (ABPM).…”
Section: Subjectsmentioning
confidence: 99%